Studi In Silico : Aktivitas Senyawa Tanaman Kecombrang (Etlingera elatior) Sebagai Kandidat Obat Antihiperurisemia: Studi Awal Pemanfaatan Kecombrang Sebagai Terapi Alternatif Gout - Muhammad Fessolsalmin; Rifda Naufalin; Putri Dian Wulansari; Susanti Susanti; Moch Herdi Nurzaman; Nitya Nurul Fadilah; Richa Mardianingrum (Jurnal Farmasi & Sains Indonesia, 2025)
Hyperuricemia is a metabolic disorder caused by an increase in uric acid levels, which is at risk of ausing gout. The plant kecombrang (Etlingera elatior) is known to contain bioactive compounds that have the potential to act as xanthine oxidase inhibitors. This study aims to evaluate 50 compounds from kecombrang as antihyperuricemia candidates using an in silico approach. The analysis includes toxicity and pharmacokinetics (ADMET) predictions, Lipinski's rule of five, molecular docking, and molecular dynamics simulations. The docking results of selected compounds Aduncetin E (-8.93 kcal/mol) and Methyllinderatin (-8.78 kcal/mol) show the best affinity for xanthine oxidase enzyme with lower binding energy compared to allopurinol (-6.26 kcal/mol). Molecular simulations support the stability of the ligand-receptor complex the MMGBSA results indicate that Aduncetin E (13.4048 kcal/mol) and Methyllinderatin (-30.3009 kcal/mol) have potential that can be developed as antihyperuricemia drug candidates.